A Project on Petrus Hispanus: Edition and Study of the Attributed Works - Meirinhos, José (2018)
Brief description of the research project Edição Crítica e Estudo das Obras Atribuídas a Petrus Hispanus – 1 / Critical Edition and Study of the Works Attributed do Petrus Hispanus – 1 (reference: FCT: PTDC/MHC-FIL/0216/2014) based at the Instituto de Filosofia da Universidade do Porto, 2016-2019.DOI: http:/dx.doi.org/10.21747/21836884/med35a8